Spatial and seasonal changes in benthic macrofauna from two dissipative sandy beaches in eastern Brazil) (Brazilian Journal of Oceanography, 2017)
Sandy beaches are dynamic ecosystems with strong interaction of sediments, waves and tidal energy, with marked effects on benthic assemblages. Although there are numerous efforts in understanding spatial-temporal variation of benthic macrofauna on sandy beaches along the southern and southeastern Marine Ecoregions in Brazil, there is poor sampling along beaches of the Eastern Marine Ecoregion (EME). Here we examined spatial and temporal scales of variability in benthic macrofauna (>; 500 µm) through a hierarchical sampling of two dissipative sandy beaches within the EME between two seasons (winter 2011 and summer 2012). We tested the hypothesis that spatial changes (i.e., meters to hundreds of meters scales) in the structure of benthic assemblages will be more pronounced compared to the weak seasonal fluctuations at this tropical region. We found weak temporal and spatial changes in sediment grain size and beach slope, but differences in macrofaunal assemblages were evident. Contrary to our hypothesis, hierarchical sampling indicated significant changes in macrofaunal composition and density at multiple local scales (meters to hundreds of meters) and on seasonal scales. The macrofauna density and composition was directly related to changes on the sediment organic matter and grain size.